Safeguarding and domestic abuse: An intersection for future policy and practice development. (1st December 2012) - McGarry, Julie; Simpson, Christine; Hinsliff-Smith, Kathryn
Abstract : There has been a growing recognition among a number of commentators that domestic abuse among older people has historically been largely 'subsumed' under the umbrella of elder abuse and that older people have been largely excluded from the discourse surrounding domestic abuse. Failure to acknowledge domestic abuse as occurring in later life, and as distinct from other forms of family violence, has in turn exerted a considerable impact in terms of the development, or a lack thereof, of appropriate services and care provision to meet the particular needs of older people who have experienced intimate partner violence (IPV). Awareness surrounding domestic abuse generally has been growing, and continues to grow in terms of visibility in both policy and practice arenas. However, it also remains unclear how current developments recognise or will explicitly address the needs of older populations. Domestic abuse in later life can be inherently complex especially where the boundaries of domestic abuse and vulnerability may be blurred. Moreover, to date there is a paucity of available literature that has attempted to explore some of the more complex aspects of domestic abuse or IPV among older populations. In this article we have primarily utilized the findings of one serous case review to illuminate both the complexities for current services and the deficit that this presents in service provision. This highlights a clear gap in current knowledge and strongly indicates a requirement for further research and development in this field of service delivery.